The Effectiveness of Hematological Indicator and Iron Biomarkers Evaluation as an Early Detection of Anemia in Adolescent Girls: A Systematic Review - Rafi’ Andyah Arum Kedaton; Nabila Sinta Devi; Kusworini Kusworini; Diadjeng Setya Wardani (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Due to elevated iron requirements during growth and menstruation, anemia in adolescent girls remains a major global health concern. Hemoglobin (Hb) testing alone has low sensitivity in detecting early iron deficiency anemia (IDA). This study aims to evaluate the diagnostic accuracy of hematological indicators (MCV, MCH, MCHC) and iron biomarkers compared to Hb alone. A systematic literature review was conducted in PubMed, Cochrane Library, SAGE Journals, ScienceDirect, Wiley Online Library, Taylor and Francis, and DOAJ, covering publications from 2015 to 2025, following PRISMA guidelines. The Joanna Briggs Institute (JBI) approach was used to assess methodological quality and risk of bias. Analysis of five relevant publications showed that Hb alone often misses subclinical iron deficiency. Sensitivity and specificity improve when combined with ferritin, soluble transferrin receptor (sTfR), and adjustments for inflammatory markers such as alpha-1-acid glycoprotein (AGP) and C-reactive protein (CRP). These findings support a multifaceted approach that integrates hematological indicators, iron biomarkers, and inflammation markers for early and accurate anemia detection in adolescent girls, in line with national and international recommendations to reduce prevalence and long-term complications.